Can I Do Both? Be Employed and Graduate? Adult Non-Traditional Learners Who Combine Employment and Higher Education Enrollment-A Look at Persistence and Best Practices to Overcoming Barriers to Improve Success and Retention - Lynn Taylor (Adult Education Research Conference, 2015)
The roundtable discussion critically analyzes two significant research studies on barriers to persistence of non-traditional adult learners who combine employment and higher education enrollment. These studies were conducted by the U.S. Department of Education in partnership with the NCES. Implications for best practices to overcome barriers, improve retention and academic success will be covered.
Keywords: non-traditional; persistence; retention; employment; higher education